Personality, Coping Strategy, and Quality of Life of Patients with Chronic Kidney Disease - Evlijn Pasha Widjast; Magdalena S Halim (Faculty of Psychology, Universitas Gadjah Mada, 2021)
Patients with chronic kidney disease are subject to prolonged medical treatment that might affect their quality of life. The purpose of this research was to investigate the correlation between personality, coping strategies, and quality of life in patients with chronic kidney disease. 40 Participants (25-55 years old) were recruited using purposive sampling and presented with three instruments: the Indonesian versions of NEO Personality Inventory-Revised (NEO PI-R), Ways of Copings, and Kidney Disease Quality of Life-36 (KDQOL-36). Results showed a significant correlation between all variables after regression analysis was applied. Further results indicate certain coping strategies were related to an individual’s perceptions of kidney disease. A significant correlation was found between three personality traits: neuroticism, extraversion and conscientiousness, and quality of life. Results also found that female patients have a better quality of life than men. Further research is needed to examine further the crucial role of social support and ethnic differences. Psychological intervention programs to provide psychoeducation on how to recognize stress symptoms and better stress management for patients with chronic kidney disease are also warranted.